Stability of multilobe hybrid bearing with short sills - Part II - Ghosh M.K.; Satish M.R. (My University, 2025)
The stability of multilobe hybrid journal bearing with short sills was investigated using the stiffness and damping coefficients. It was found that that multilobe hybrid bearings with short sills could give better dynamic performance and stability relative to circular hybrid bearings when the offset factor was more than one. It was also found that the four lobe hybrid bearings exhibited better stability than three lobe hybrid bearings.